IDIOPATHIC SUDDEN SENSORINEURAL HEARING LOSS: CURRENT INSIGHTS INTO ETIOLOGY, DIAGNOSIS AND MANAGEMENT - Cvorovic, Professor Ljiljana; Jotic, Ana; Bukurov, Bojana; Djuric, Nebojsa (Medical Research, 2025)
Idiopathic sudden sensorineural hearing loss (ISSNHL) is a distinct otologic emergency characterized by an abrupt onset of unilateral sensorineural hearing loss, typically occurring within 72 hours and lacking any identifiable cause. Although its pathogenesis remains incompletely understood, several mechanisms have been proposed, including cochlear microvascular insufficiency, viral or autoimmune-mediated inner ear inflammation, intracochlear membrane rupture, and stress-induced cellular responses.The diagnostic algorithm requires prompt audiological assessment, exclusion of alternative etiologies, and, where indicated, neuroimaging, particularly utilizing advanced modalities such as three-dimensional fluid-attenuated inversion recovery (3D-FLAIR) magnetic resonance imaging (MRI). Systemic corticosteroids remain the mainstay of treatment, while intratympanic steroid injections and hyperbaric oxygen therapy are increasingly employed as adjunctive or salvage therapies. Treatment outcomes vary considerably and are influenced by multiple prognostic factors, including patient age, severity of hearing loss, presence of vertigo, timing of therapeutic intervention, and underlying vascular or metabolic comorbidities.This review synthesizes current evidence on the etiopathogenesis, clinical presentation, diagnostic approach, and management strategies for ISSNHL, drawing on recent systematic reviews, clinical guidelines, and original research. Special attention is given to pediatric and bilateral cases, as well as to emerging diagnostic and therapeutic modalities. A more refined understanding of the heterogeneous nature of ISSNHL is essential for guiding individualized clinical decision-making and optimizing patient outcomes.
Keywords: idiopathic sudden sensorineural hearing loss, sensorineural hearing loss, corticosteroid, hyperbaric oxygen therapy, 3D-FLAIR MRI, prognosis